Qualitative Insights on Arts and Sciences Faculty Evaluation from Students in a Philippine State College - Pontillas, Marlon S.; Sallao, Karla Mae S.; Requinala, Kharl Vincent T. (International Journal of Educational Studies, 2025)
This study aims to assess the student evaluations of teaching (SETs) at the College of Arts and Sciences (CAS) of Camarines Sur Polytechnic Colleges (CSPC) to establish various strengths and weaknesses in the faculty performance. Filling the research gap in qualitative data analysis in SETs, the study employs content analysis of the open-ended responses for four rating times in two academic years. The elements that emerged as positive include the relevance of course content to practice, faculty understanding and caring, faculty competence as teachers, and organizational and communicative qualities of teaching. On the other hand, areas that warrant development concern the rate of teaching, availability of additional learning resources, consistent class timetable, and feedback. Observations of the study identify that student appreciate a positive and stimulating atmosphere and good teaching and organization of learning materials. According to these findings, recommendations include the following: increasing the faculty training in adaptive pacing, empathetic interaction, and clear communication with the help of institutional resources for supplementary materials and feedback systems. This approach can enhance student learning and improve the compatibility of faculty practices with the current and future students’ requirements.